Sampling of Airborne dust in heavily laden atmosphere - Ganguli, S. C.; Gupta, B.K. Datta; Ganguli, N. K. (Defence Science Journal, 2014)
The U.S. Bureau of Mines Sugar Tube Type B for determining rock dust in air has been modified to give higher filtering efficiency in a heavily laden atmosphere.